Ex-ante regulation and ex-post liability under uncertainty and irreversibility: governing the coexistence of GM crops - Volker Beckmann; Claudio Soregaroli; Justus Wesseler (Kiel Institute for the World Economy (IfW), 2009)
Ex-ante regulations and ex-post liabilities for using a new technology will induce additional costs for adopters. The standard model is advanced by including irreversibility and uncertainty and taking into account transaction costs of negotiating possible cost reductions. The case analysed is the coexistence policy for GM crops in the European Union. Results show, the design of the rules and regulations can provide strong incentives for regional agglomeration of GM and non-GM farmers.
Keywords: D81; L23; Q12; Q24; R3; 330; Ex-ante regulation; ex-post liability; irreversibility; uncertainty; Agglomeration; Regulierung; Produkthaftung; Innovationsdiffusion; Irreversibility of Investment; Novel Food; Gentechnik; Agrarbiotechnologie; Regionale Konzentration; Theorie; EU-Staaten